Vasculitis as an indicator of disease severity in familial Mediterranean fever - Barzilai, Aviv; Mash, Yarin; Gershon, Rotem; Pras, Elon; Baum, Sharon (Frontiers in Immunology, 2025)
IntroductionVarious types of vasculitides have been identified in patients with familial Mediterranean fever (FMF); however, FMF characteristic in patients who experience vasculitis during the disease course have not been described. This study aimed to describe the types of vasculitides in FMF and characterize the patients.MethodsThis nested case-control study compared 27 patients with FMF (12 male) diagnosed with vasculitis with 100 patients (49 men) who did not develop vasculitis.ResultsMost patients (25/27) developed vasculitis after FMF diagnosis. Four types of vasculitides were observed: cutaneous small vessel vasculitis (10 patients, 37%), Henoch–Schonlein purpura/immunoglobulin A vasculitis (8 patients, 30%), periarteritis nodosa (three patients, 11%), and Behçet disease (six patients, 22%). The vasculitis group was younger at FMF onset (6.6 [± 5.9] years vs. 16.2 [± 13.7] years, p < 0.002) and diagnosis (13.1 [± 13.1] years vs. 25.1 [± 17.92] years, p < 0.001). This group showed a higher frequency of homozygosity for the M694V mutation (73.9% vs. 29.4%, p < 0.001), had a more severe FMF (mean Pras severity score: 10.4 [± 2.6] vs. 7.3 [± 3.1], p < 0.001), required higher colchicine doses (1.96 [± 0.61] mg/d vs. 1.66 [± 0.65] mg/d, p < 0.025), and tended to show higher rates of colchicine resistance (29.6% vs. 12%, p = 0.053). However, vasculitis was not an independent factor influencing FMF severity.ConclusionPatients with FMF and vasculitis are characterized by a more severe disease, likely due to factors other than vasculitis itself. Yet, its presence can serve as a clinical clue to disease severity.